Incidencia de las actividades productivas de la panela de caña de azúcar en la calidad ambiental del entorno - Peñarrieta Macías, Fabián Fabricio (2015)
The research has as its main objective the determination of the agrotourism offer for Junín canton in the province of Manabi allowing to boost agricultural resources and contribute to the socioeconomic development of the territory. For the development of the research we proceeded to make the situational analysis with various phases, in addition to using descriptive method, direct observation and field research, it envisioned that Junín canton has a territory characterized by production agricultural, and that there has attractions that meet the expectations of tourists who visit it. Market research proceeded to make the identification of supply and demand was performed using data collection tools such as the survey, in addition to the descriptive method and direct observation. This was identified and evaluated the existing resources according to the potential. As the final phase potentiated the agrotourism offer was determined through circuits; including requirements for such infrastructure improvements; proposals raised as communication strategies designed to reach the tourist by different media such as the Web and agreements with institutions. It is concluded that a proposed agro tourism offer to the Junín canton allow the main sectors involved in agricultural activities and existing resources can structure tourism products that are of interest to tourists seeking to get in touch with nature.